LA ÉTICA EMPRESARIAL COMO CREACIÓN DE VALOR - Vega Centeno, Maximo Ugarte (2007)
The century change has brought new demands in the economy, the technology and the Internet, that have accentuated the popularization of knowledge and the increment of the social role of the companies, in the advance of the organizations, as well as the growing paper in the societies. In this context, the ethics arises as creation of value, in reason of the transparency of the managerial behaviors that benefit the whole community and the company itself, besides avoiding the juridical-legal consequences, that would happen as a result of its non-practice.